Writing essays using e-book writing application: analyses of teacher candidates' interactive narratives - Kee, Li Li; Razali, Abu Bakar (Mehran University of Engineering Technology, 2022)
The study adopted a qualitative research approach, with interactive narratives from six teacher candidates in one Institute of Teacher Education (ITE) being analyzed using the document analysis technique. It seeks to investigate the use of e-book writing applications in improving narrative writing among teacher candidates. Teacher candidates learned about narrative writing using the process approach. They are taught how to create interactive narratives using Flipsnack. Predetermined codes were used to analyze the interactive narratives. The findings reveal that using the e-book writing application improves the teacher candidates’ narrative writing, as evidenced by the improved genre and message accuracy, task requirements fulfilment, use of grammar and vocabulary, originality, coherence and cohesion, and use of multimedia elements. This further suggests that using the e-book writing application to produce interactive narratives can benefit teacher candidates by exposing them to a more meaningful, enjoyable, and engaging way of writing narratives.